Chronic recurrent multifocal osteomyelitis causing spinal cord compression - Baulot, E. (Springer-Verlag, 1998)
Chronic recurrent multifocal osteomyelitis (CRMO) is a very rare condition of unknown etiology and most commonly occurs during childhood or adolescence. The purpose of this paper is to present a case of CRMO in a vertebral location with severe kyphosis, spinal cord compression, and neurological dysfunction requiring anterior decompression and fusion. After 12 weeks, the patient was physically able to return to school. At 2-year follow-up, neurological and functional outcomes are fair. Magnetic resonance imaging shows good restoration of the sagittal spine alignment despite residual mild kyphosis, and restoration of a normal sagittal diameter of the spinal canal.